PENGARUH MEDIA SOSIAL TERHADAP PENJUALAN PRODUK CAMILAN LOKAL SECARA ONLINE - Indah Handaruwati (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
Technological developments such as the existence of social media is now widely used as a sales promotion tool. This encourages local marketers of snack products to create an account on social media in this case is facebook. Marketers who are mostly small and medium-sized businesses do various activities in social media to get closer to their buyers, which in turn can increase sales of their products. The purpose of this study is to to describe the activities of local snack marketers in facebook social media and to know what factors in facebook social media that can affect the sale of local snack products online. MethodThis research is quantitative. The sample size is 30 respondents of local snack product marketers through social media facebook. Sampling is done by purposive sampling technique that is sampling done to someone who fulfill the criteria of having local snack business, having at least one active local snack facebook account, actively doing marketing activity in the account. In this research, there are two variables, namely facebook social media variables are Knowledge Level, Number of Friends, Activity in Social Media and Completeness of Product Information (X) and local snack product sales variables online (Y). Analysis in this research using multiple linear regression analysis. The results achieved in this research is that all four dimensions of social media facebook all have a significant influence on sales of local snack products online which is Social Media Knowledge Level factor of 34.44%, Number of Friends by 25.64%, Social Media Activity of 57.57% and completeness Product Information is 40.05%. Keywords: social media, online sales